PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEB PADA SISWA KELAS IX TENTANG BAGIAN-BAGIAN MESIN BUBUT DI SMK N 12 BANDUNG - Alamsyah Pratama, - (2022)
The purpose of this research is to determine the interactive Web-based learning media that can be used for learning and to analyze the data on the effect of the application of web-based learning media on improving student learning outcomes on the material of lathe parts. this is because face-to-face learning of introductory practicum theory is replaced by online learning so that the two-way learning process is difficult and causes a lack of understanding of class IX Aircraft Component Machining students regarding the main parts of a lathe, to overcome this, an interesting and interactive learning media is needed. The method in this study uses R&D (Research and Development) and uses a one group pre test post test research design. Sampling in this study used a random sampling technique with the research subjects were students of class IX Aircraft Component Machining on the subject of turning aircraft components, researchers took a sample of 40 people. The learning media products that have been made are suitable for use based on the validation of material experts and media experts with appropriate categories. The results of this study indicate an increase in learning outcomes when viewed from the average pre-test score of 49,75 and the average post-test score of 77,5. As well as with the acquisition of a significance test using a t-test (Paired Sample t-test) with a significance value of 0,000, this increase was caused by the use of learning media that had been made, so that the use of this learning media had a good impact in improving students' understanding of the component turning subject, aircraft. In addition, this learning media also adds insight to students in using technology, especially websites for learning purposes.